Existential Films on Beauty, Community and Creativity: Exploring Ways of Integrating Mental Health Insights into the Theological Discussion on Loss and Grief - Panayiotis Thoma (Religions, 2026)
It is commonly accepted by mental health professionals who work in the area of death and grief that both the help which communities may offer to the bereaved and creativity may prove decisive factors in their recovery after loss; the article aims to introduce specific existential films to the discussion about the value of both. Communality and creativity are also key ecclesiological and theological concepts. They are integral parts of the life of ecclesiastical communities, which honor the memory of the dead and have a duty to stand by their mourning members. These concepts may therefore create a bridge between spirituality and psychology/psychiatry, encouraging church leaders and health professionals to cooperate in addressing the needs of the bereaved. In the above-described context, films like Terrence Malick’s The Tree of Life (2011), Rachid Buchareb’s London River (2009) and the short animation film Lila (2014) by Carlos Lascano may become valuable resources. Firstly, for challenging questionable religious responses to death while also discovering beauty in natural and community life in spite of/through loss, as well as embracing the memory of the deceased through creativity. As the latter has been characterized by relevant bibliography in death studies as both a form of expressing grief and a therapeutic process, it is also a crucial calling for the faithful to remain creative in the image and likeness of their Creator. In the discussion of the films, these links between theological/spiritual and psychological/mental health perspectives are explored with regard to both preparing for death and responding to it through joint efforts or lessons at schools.